2020
DOI: 10.3390/app10186619
|View full text |Cite
|
Sign up to set email alerts
|

Noise Prediction Using Machine Learning with Measurements Analysis

Abstract: The noise prediction using machine learning is a special study that has recently received increased attention. This is particularly true in workplaces with noise pollution, which increases noise exposure for general laborers. This study attempts to analyze the noise equivalent level (Leq) at the National Synchrotron Radiation Research Center (NSRRC) facility and establish a machine learning model for noise prediction. This study utilized the gradient boosting model (GBM) as the learning model in which past noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…However, few attempts have been made to use gradient boosting to predict noise. Therefore, the NSRRC designed a model based on the GBM to predict noise, which provides more accurate noise distribution prediction results than multiple linear regression (MLR) [27]. Consequently, in the present study, the GBM was selected as the machine learning model of propose approach for motor noise masking simulation, and random forests (RF), support vector machine (SVM), gaussian processes regression model (GPRM) and multiple linear regression (MLR) were very common prediction models in above literature and may performed as compare method to predict acoustic noise.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, few attempts have been made to use gradient boosting to predict noise. Therefore, the NSRRC designed a model based on the GBM to predict noise, which provides more accurate noise distribution prediction results than multiple linear regression (MLR) [27]. Consequently, in the present study, the GBM was selected as the machine learning model of propose approach for motor noise masking simulation, and random forests (RF), support vector machine (SVM), gaussian processes regression model (GPRM) and multiple linear regression (MLR) were very common prediction models in above literature and may performed as compare method to predict acoustic noise.…”
Section: Methodsmentioning
confidence: 99%
“…The term F(xt) represents the target prediction model. Test samples are input into this model to obtain noise prediction results [27,29,30,34,35]. Algorithm is presented in the following text.…”
Section: A Gradient Boosting Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the services to be provided, it is the characterization of the possible main sources of noise in the city. Noise analysis is also an area of research in which machine learning has been shown to have a wide range of applications, being one of them, the prediction of traffic volume as a function of vehicle generated noise as in Alam et al [ 14 ] or to determine noise prediction in industrial scenarios [ 15 ]. From our point of view, we can apply this knowledge in the field of smart cities to determine the main sources of noise at specific points in the city and thus provide more detailed information to public administrations in order to take the best measures to help mitigate that source of noise.…”
Section: Introductionmentioning
confidence: 99%